Հոգևոր և աշխարհիկ իշխանությունների փոխհարաբերությունները Արևելյան Վրաստանում (XVI-XVIII դդ.) - Գոռ Մարգարյան (ՀՀ ԳԱԱ հրատ.)
В Восточной Грузии церковь всегда играла важную роль в культурной, политической жизни страны. В XVI-XVIIIвв. церковь в лице Мцхетского католикосата строила свои отношения не только с местными царями, но и с шахами Ирана, посколько во второй половине XVI века Восточная Грузик оказалась под властью Ирана.In late Middle Ages, the church in Eastern Georgia was a serious political power. It had juridical, administrative rights and a high degree of freedom. In the XVI-XVIII centuries the Georgian church had built its relations not only with the local rules, but with the shahs of Iran as well.
Keywords: History